2000
DOI: 10.1039/b000995o
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and characterising sources of persistent organic pollutants (PAHs and PCBs) in surface sediments of an industrialized area (harbour of Trieste, northern Adriatic Sea)

Abstract: A sediment sampling based on a two-dimensional mapping was performed in the harbour of Trieste (northern Adriatic Sea), considering 28 sites exposed to pollutant inputs from harbour and industrial activities. Polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) were determined in surface sediments, because these very persistent pollutants seem to be responsible for the depletion of benthic populations observed in this area. The correlation matrix indicates that PAHs and PCBs are non-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…order of magnitude) of the ΣPAHs values can be made. With that in mind, the level of contamination in Mar Grande was higher than the one reported for the Adriatic Sea 32,34 , (except for the Venice Lagoon 31 and the Trieste harbour 33 Sediment chemistry data alone do not provide an adequate basis for assessing the hazards posed by sediment-associated contaminants to aquatic organisms. Interpretive tools are also required to determine if sediment-associated contaminants are present at concentrations which could, potentially, impair the designated uses of the aquatic environment.…”
Section: Resultsmentioning
confidence: 65%
“…order of magnitude) of the ΣPAHs values can be made. With that in mind, the level of contamination in Mar Grande was higher than the one reported for the Adriatic Sea 32,34 , (except for the Venice Lagoon 31 and the Trieste harbour 33 Sediment chemistry data alone do not provide an adequate basis for assessing the hazards posed by sediment-associated contaminants to aquatic organisms. Interpretive tools are also required to determine if sediment-associated contaminants are present at concentrations which could, potentially, impair the designated uses of the aquatic environment.…”
Section: Resultsmentioning
confidence: 65%
“…This is probably due to the inputs of persistent organic pollutants originating from the nearby harbor of Trieste (Adami et al 2000). To a lesser extent, as already stated by Faganeli et al (1991), the industrial activities in the Koper Bay (Slovenia) and the main anticlockwise circulation of the water could justify TOC contents in the transect A (1.07±0.05%).…”
Section: Total Organic Carbon and Total Nitrogen Distributionmentioning
confidence: 76%
“…The results of primary component analysis showed that in the first component, the coefficients for Baa, Bbf, Bkf, Bap, I1p, and Daa are high (see factor 1 of Table 5), also indicating they have the same source. Adami et al (2000) proposed that in river sediments, if the concentration ratio of phenanthrene (Phe) to acenaphthene (Ant) was greater than 10, PAHs were mainly from petroleum sources, while if Phe/Ant \10, PAHs were mainly from coal combustion. Rogge et al (1993) discovered that if the concentration ratio of fluoranthene (Fla)/Pyr [1, the combustion source is mobile exhaust, while Fla/Pyr \1 means the main source is from petroleum.…”
Section: Resultsmentioning
confidence: 99%